Pengaruh Gender Diversity of Signing Auditors terhadap Kualitas Audit: Studi Empiris pada Perusahaan Sektor Consumer Cyclicals yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2021 - Titania Febiola; Istianingsih Istianingsih; Aloysius Harry Mukti (Penerbit Goodwood, 2023)
Purpose: This study aims to test whether there is an effect of gender diversity of signing auditors on audit quality in consumer cyclical sector companies listed on the Indonesia Stock Exchange in 2019-2021. Methodology: The variables used in this study are audit quality as the dependent variable, gender diversity of signing auditors as the independent variable, and company size, leverage, and inventory as control variables. The data analysis method used in this research is descriptive statistical analysis, classical assumption test, and multiple linear regression test. The results of the study show that gender diversity of signing auditors has no effect on audit quality as measured by earnings management. Firm size has a positive effect on audit quality, leverage has no effect on audit quality and inventory has a positive effect on audit quality. Results: The results of this study are used case diagrams and class diagrams for modeling online queuing systems for patient visits in Puskesmas. It can be used during the application program development and implementation stage of an online queuing system for outpatient visits in Puskesmas. Limitations: This research whose data were obtained from the Indonesia Stock Exchange with a total oobservationsof 87 years of companies.